Transport and the Village in Sub-Saharan Africa - Ian Barnwell (2012)
Past efforts to improve rural transport in Sub-Saharan Africa (SSA) have focused principally on building and maintaining roads. The issues of rural access, mobility and household transport were paid little attention. This study emphasizes the significance of village-level transport in meeting the basic subsistence needs of rural households. A series of five surveys on village-level travel and transport, complemented by case studies, was carried out through the Rural Travel and Transport Program (RTTP) under the Sub-Saharan Africa Transport Policy Program. These surveys and studies covered five areas of three countries in SSA: Burkina Faso, Uganda, and Zambia. Eight hundred forty (840) households in 42 villages were covered by the investigation. The five areas cover a range of different physical environments from the Sahel to the Savanna and Montage ecosystems and contain examples of both dispersed and nucleated settlements, as well as different population densities.